Harnessing Digital Urbanism and Blockchain for Smart Urban Transformation - El-Masry, Omar; Abdelrahman, Laila (TOPAZART, 2025)
This case study explores Cairo City’s transformation into a digitally empowered metropolis through the integration of blockchain technology and data-driven urban research. As one of the largest cities in the Global South, Cairo faces significant challenges stemming from rapid urbanization, bureaucratic inefficiencies, and socio-economic disparities. The study investigates how emerging technologies—particularly blockchain, alongside qualitative and quantitative research tools like NVivo 12—are being used to address issues in urban governance, service delivery, and citizen participation. Through interviews, surveys, and document analysis, the research highlights improvements in transparency, efficiency, and trust in systems such as land registration, subsidy distribution, and digital identity management. Findings show increased confidence in digital services, particularly among youth and educated populations, though barriers such as the digital divide, data privacy concerns, and limited institutional capacity remain. Cairo’s experience demonstrates the transformative potential of integrating blockchain with inclusive, evidence-based policymaking. The study underscores the importance of investing in digital infrastructure, legal frameworks, and multi-stakeholder collaboration to ensure equitable and sustainable urban governance in megacities worldwide.